Idahotyphlus alleni Gusarov, gen. n., sp. n., a new leptotyphline staphylinid beetle from Idaho (Coleoptera: Staphylinidae: Leptotyphlinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
Idahotyphlus alleni Gusarov, gen. n. & sp. n. (tribe Neotyphlini) is described from Idaho. Diagnostic characters and illustrations are provided to distinguish Idahotyphlus from its most-closely related genera.